Increased Intestinal Microbial Diversity Following Fecal Microbiota Transplant for Active Crohn's Disease. Issue 9 (September 2016) - Vaughn, Byron P.; Vatanen, Tommi; Allegretti, Jessica R.; Bai, Aiping; Xavier, Ramnik J.; Korzenik, Joshua; Gevers, Dirk; Ting, Amanda; Robson, Simon C.; Moss, Alan C.
Abstract : Background: The microbiota in the lumen of patients with Crohn's disease (CD) is characterized by reduced diversity, particularly Firmicutes and Bacteroidetes. It is unknown whether the introduction of the intestinal microbiota from healthy individuals could correct this dysbiosis and reverse mucosal inflammation. We investigated the response to fecal microbial transplantation (FMT) from healthy individuals to subjects with active CD. Methods: We performed a prospective open-label study (uncontrolled) of FMT from healthy donors to subjects with active CD. A single FMT was performed by colonoscopy. Recipients' microbial diversity, mucosal T-cell phenotypes, and clinical and inflammatory parameters were measured over 12 weeks, and safety over 26 weeks. Results: Nineteen subjects were treated with FMT and completed the study follow-up. Fifty-eight percent (11/19) demonstrated a clinical response (Harvey–Bradshaw Index decrease >3) following FMT. Fifteen subjects had sufficient pre/postfecal samples for analysis. A significant increase in microbial diversity occurred after FMT ( P = 0.02). This was greater in clinical responders than nonresponders. Patients who experienced a clinical response demonstrated a significant shift in fecal microbial composition toward their donor's profile as assessed by the Bray–Curtis index at 4 weeks ( P = 0.003). An increase in regulatory T cells (CD4 + CD25 + CD127lo) was also noted in recipients' lamina propria following FMT. No serious adverse events were noted over the 26-week study period. Conclusions: In this open-label study, FMT led to an expansion in microbial bacterial diversity in patients with active CD. FMT was overall safe, although the clinical response was variable. Determining donor microbial factors that influence clinical response is needed before randomized clinical trials of FMT in CD. Abstract : Supplemental Digital Content Is Available in the Text.Article first published online 10 August 2016.